A numerical simulation validated experimentally for thermally developing convection characteristics of a phase change nanofluid flow in a circular tube. (June 2021) - Ho, C.J.; Chu, Yu-Chao; Huang, Z.P.; Yang, T.S.; Chiu, T.C.; Chen, Bo-Lin; Yan, Wei-Mon
Abstract: The present work aims to examine the heat transfer effectiveness of laminar forced convection for water-based Nano-PCM emulsion flow through a pipe. Over a finite length of the wall, the pipe is uniformly heated with a uniform heating flux. An approximate enthalpy model is employed for the formulation of the energy equation to present the phase-change process of the Nano-PCM emulsion. Efficiency of utilizing the water-based Nano-PCM emulsion to substitute its base fluid as the working fluid in a uniform heating pipe was then demarcated quantitatively for different dimensionless parameters including the mass concentration of the Nano-PCM particles, ω pcmp, and the modified Stefan number, S t e b f ∗ . Predicted results show that the surface-averaged cooling efficiency of the nanofluid appears increasingly promoted with its Nano-PCM particle fraction under decreasing S t e b f ∗ . The local heat transfer coefficient can be improved more than 20 times as the phase change fluid with ω pcmp = 10% and S t e b f ∗ = 0.01 is used. The local heat transfer improvement for the phase change nanofluid over the water is directly related to the mass fraction of Nano-PCM particle. The averaged heat transfer effectiveness of water-based Nano-PCM emulsion flow is considerably increased with its Nano-PCM particle fraction under decreasing S t e b f ∗ .